Peranan Audit Forensik Dalam Mencegah Kejahatan Keuangan Perbankan Dengan Menggunakan Teknologi Informatika - Nur, Aryanto; Suhada, Suhada (CV. ITTC INDONESIA, 2024)
Financial crime is any activity that involves fraudulent or criminal behavior to gain personal financial gain. This is a criminal activity carried out by individuals or groups involved in financial crime activities, such as: money laundering, terrorism financing, fraud, tax evasion and identity theft. Financial crime has become a big problem and is detrimental to many parties, using increasingly sophisticated techniques, which requires a solution. In this research the author will focus on discussing banking financial crimes using information technology, because they seriously damage the reputation of financial institutions, destroy public trust, and cause significant financial losses. Banking must have a strategy to protect various technologies, information and data simultaneously, which requires coordination with all stakeholders in Indonesia. The aim of writing this journal is to determine trends, patterns, factors that influence, anticipate and punish banking financial crimes using information technology. The research uses qualitative methods with data collection methods using literature studies. The object of this research is secondary data in the form of banking financial crimes using information technology committed by perpetrators of banking financial crimes. The role of forensic audit is the best way to prevent and detect banking financial crimes using information technology in Indonesia. Forensic audit has the ability to provide statements based on its expertise.